Aerially Applied Zinc Oxide Nanoparticle Affects Reproductive Components and Seed Quality in Fully Grown Bean Plants (Phaseolus vulgaris L.) - Salehi, Hajar; Chehregani Rad, Abdolkarim; Sharifan, Hamidreza; Raza, Ali; Varshney, Rajeev K. (Frontiers in Plant Science, 2022)
The development of reproductive components in plant species is susceptible to environmental stresses. The extensive application of zinc oxide nanoparticles (nZnO) in various agro-industrial processes has jeopardized plant's performance and functionality. To understand the response of the developmental (gametogenesis and sporogenesis) processes to nanoparticles (NPs) exposure, the aerial application of nZnO and their ionic counterpart of ZnSO4 at four different levels were examined on bean plants (Phaseolus vulgaris) before the flowering stage. To evaluate the mentioned processes, briefly, flowers in multiple sizes were fixed in paraffin, followed by sectioning and optical analysis. The possibility of alternations in reproductive cells was thoroughly analyzed using both light and electron microscopes. Overall, our results revealed the histological defects in male and female reproductive systems of mature plants depend on NPs levels. Further, NPs caused tapetum abnormalities, aberrations in carbohydrate accumulation, and apoptosis. The nZnO induced abnormal alternations right after meiosis and partly hindered the microspore development, leading to infertile pollens. The seed yield and dry weight were reduced to 70% and 82% at 2000 mg L-1 nZnO foliar exposure, respectively. The sodium dodecyl sulfate (SDS) -polyacrylamide gel electrophoresis pattern showed the increased expression of two proteins at the molecular weight of 28 and 42 kDa at various concentrations of nZnO and ZnSO4. Overall, our results provided novel insights into the negative effect of nano-scaled Zn on the differential mechanism involved in the plants' reproductive stage compared to salt form.